2010
DOI: 10.1096/fj.10-155507
|View full text |Cite
|
Sign up to set email alerts
|

A single‐molecule force spectroscopy nanosensor for the identification of new antibiotics and antimalarials

Abstract: An important goal of nanotechnology is the application of individual molecule handling techniques to the discovery of potential new therapeutic agents. Of particular interest is the search for new inhibitors of metabolic routes exclusive of human pathogens, such as the 2-C-methyl-D-erythritol-4-phosphate (MEP) pathway essential for the viability of most human pathogenic bacteria and of the malaria parasite. Using atomic force microscopy single-molecule force spectroscopy (SMFS), we have probed at the single-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 81 publications
(92 reference statements)
3
32
0
Order By: Relevance
“…While this work was being prepared, a study describing single-molecule force spectroscopy for the identification of novel DXP synthase inhibitors was reported (14). The method allows measurement of adhesion forces between immobilized substrates and enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While this work was being prepared, a study describing single-molecule force spectroscopy for the identification of novel DXP synthase inhibitors was reported (14). The method allows measurement of adhesion forces between immobilized substrates and enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest a possible dissociation of substrate recognition properties and substrate transformation properties that could permit the use of this catalytically less active nanosensor as a tool for identifying high affinity ligands without the need for substrate turnover. Interestingly, Sisquella et al (14) reported binding of GAP tethered through the phosphoryl moiety and enhancement of its affinity for the enzyme in the presence of soluble pyruvate. This is particularly interesting, in light of our finding that removal of the phosphoryl moiety inverts the binding mode of the acceptor aldehyde.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent work by Sisquella et al with E. coli DXPS using single-molecule force spectroscopy also supported an ordered mechanism in which pyruvate binds tightly, and GAP binds before the reaction occurs. 19 This precedent within the enzyme family demonstrates that experimental evidence is required to establish the kinetic mechanism of MenD.…”
mentioning
confidence: 99%
“…Another direct application of the AFM principle for the search for bio-active compounds is the single-molecule force spectroscopy (Figure 4) [28]; the authors elected to screen for new inhibitors of the 2- C -methyl- d -erythritol-4-phosphate (MEP) pathway designed to specifically affect members of the kingdom bacteria, including human pathogens, such as malaria parasites, but not members of the kingdom animalia (see refs. [29,30], and below for details).…”
Section: Applications Of Nanotechnology To Life Sciencesmentioning
confidence: 99%